Responsabilidad civil médica y aplicación de levantamiento del velo societario - Duffoo Quintos, Mayra Alejandra (2020)
In the present research work, an analysis of a strategy used by medical establishments is carried out today, aimed at evading or limiting responsibility when creating legal persons to interact with the medical professionals that make up their staff. Therefore, adding some elements of civil responsibility, we seek to use the legal figure of the lifting of the corporate veil, making a simile with its use in labor law, in order to attribute responsibility to all subjects that are involved in these complex relationships so that the subject harmed by the event that caused damage can be properly compensated.